Interdisciplinary Systematic Review: A Novel Approach to Evidence Synthesis (The Reasoner, 2025)
Reporting on the newly started project "Interdisciplinary Systematic Review: A Novel Approach to Evidence Synthesis"
Keywords: intervention; EBM; mechanistic evidence; epistemic injustice; interdisciplinary systematic review